Концепция комплексного подхода при проектировании средств телекоммуникаций с учетом требований ЭМС - Невлюдов, И. Ш.; Стародубцев, Н. Г.; Демская, Н. П. (Харьковский национальный университет радиоэлектроники, 2015)
Formulate the essence of an integrated approach to cross-cutting electromagnetic design as an optimal solution to ensure the requirements of the electromagnetic compatibility of radio electronic means in the construction of which consists in taking into account all constraints and optimality criteria at each stage of the design and a holistic view of the finished product throughout the product lifecycle. For a process of optimal design of radio-electronic means with a view to ensuring the electromagnetic compatibility requirements put forward the following key principles: multi-stage, the optimal way, the unification of models of complex methods, a sufficient degree of accuracy, adaptation.
Keywords: электромагнитная совместимость; жизненный цикл; беспроводные сети связи